Changes in hemoglobin oxidation and band 3 during blood storage impact oxygen sensing and mitochondrial bioenergetic pathways in the human pulmonary arterial endothelial cell model - Jana, Sirsendu; Kassa, Tigist; Wood, Francine; Hicks, Wayne; Alayash, Abdu I. (Frontiers in Physiology, 2023)
Red blood cells (RBCs) undergo metabolic, oxidative, and physiological changes during storage collectively described as the "storage lesion". The impact of storage on oxygen hemostasis following transfusion is not fully understood. We show that RBCs storage induces changes in oxygen binding that were linked to changes in oxygen sensing (hypoxia-inducible factor, HIF1-α) mechanisms and mitochondrial respiration in human pulmonary arterial endothelial cells (HPAECs). A drop in oxygen affinity (P50) to approximately 20 from 30 mmHg was seen at the first week but remained unchanged for up to 42-days. This led to suppression of HIF-1α in the first 3 weeks due to limited oxygen supplies by RBCs. Also noted, membrane oxidative damage, band 3 alterations, and subsequent microparticles (MPs) formation. Mass spectrometric analysis revealed the upregulation of transitional endoplasmic reticulum ATPase, essential for clearing ROS-damaged membrane proteins and the protein DDI1 homolog, a proteasomal shuttle chaperone. Band 3 complex proteins and superoxide dismutase were among the downregulated proteins. Mitochondrial oxygen consumption rates measured in HPAECs incubated with RBCderived MPs (14-day and 42-day) showed a rise in maximal respiration. Interventions strategies that target intracellular hemoglobin (Hb)'s redox transitions and membrane changes may lead to reestablishment of oxygen homeostasis in old RBCs.